1989
DOI: 10.1128/mcb.9.9.3808
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of the human MDR (P-glycoprotein) gene family.

Abstract: The human MDR (P-glycoprotein) gene family is known to include two members, MDR] and MDR2. The product of the MDR] gene, which is responsible for resistance to different cytotoxic drugs (multidrug resistance), appears to serve as an energy-dependent efflux pump for various lipophilic compounds. The function of the MDR2 gene remains unknown. We have examined the structure of the human MDR gene family by Southern hybridization of DNA from different multidrug-resistant cell lines with subfragments of MDR] cDNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(121 citation statements)
references
References 50 publications
1
119
0
1
Order By: Relevance
“…This data was expected considering that the mdr-1, the lrp and the mrp genes belong to the human normal genome. Moreover, particularly for mdr-1, a number of authors using different techniques have already shown that these genes are physiologically expressed in almost all normal cells and tissues (Chin et al, 1989;Weinstein et al, 1990;Pileri et al, 1991). A second point that must be stressed is that, at least for PGP, it has been already shown that the grade of multidrug resistance expressed by a cell line depends on the level at which the mdr-1 is expressed rather than on the simple presence or absence of any mdr-1 expression (Choi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This data was expected considering that the mdr-1, the lrp and the mrp genes belong to the human normal genome. Moreover, particularly for mdr-1, a number of authors using different techniques have already shown that these genes are physiologically expressed in almost all normal cells and tissues (Chin et al, 1989;Weinstein et al, 1990;Pileri et al, 1991). A second point that must be stressed is that, at least for PGP, it has been already shown that the grade of multidrug resistance expressed by a cell line depends on the level at which the mdr-1 is expressed rather than on the simple presence or absence of any mdr-1 expression (Choi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Biology of the Cell onstrated that this Sfi fragment and a 120-kb Sfi fragment comprise the nonamplified native MDR1/MDR2 locus and are present in the amplified copies of the MDR1 and MDR2 genes in KB-C4 (Chin et al, 1989;Lincke et al, 1991). Therefore, no gross DNA rearrangements occurred at the MDR locus during the early amplification events that generated the submicroscopic circular 890-kb DNA amplicon in cell lines KB-ChR-8-5-11 and KB-Cl nor during later amplification events that generated the DM structures comprised of covalently closed dimers and tetramers of the 890-kb "unit" amplicon in the colchicine-resistant cell lines KB-CB1.5, KB-C4, and KB-C6 ( Figure 7B).…”
Section: ~~~~~~~~~~~~~~~~~~~~~~~~~~M Olecularmentioning
confidence: 99%
“…MDR1 is a large gene, spanning more than 100 kb on chromosome 7, with 28 exons that are spliced into a 4.5-kb mRNA. The encoded P-glycoprotein is a highly conserved member of the ABC transporter family with 12 membrane spanning domains, two nucleotide binding domains, and a molecular weight of approximately 170 kDa (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%